Epidemiology of Obesity and Associated Comorbidities - Andolfi, Ciro; Fisichella, P Marco (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2018)
Obesity currently affects 78.6 million people (33%) in the United States and is expected to increase to over 50% of the population by 2030. This epidemic is fueled by the growing rate of obesity in adolescents. The new science of obesity indicates that there is a tipping point at which genetic resetting occurs and it is reached when adipose tissue dysfunction occurs. It is becoming clear that obesity is less an ongoing personal choice than a fact of biology. With this review, we aim to describe the epidemiology of obesity and the associated comorbidities.